Most impacted countries by the health crisis caused by COVID-19 in the world up to 08/29/2022 - Mora-Alvarado, Darner A. (2023)
This study addresses the impact of the health crisis caused by COVID-19, whose causal agent is the SARS-CoV-2 virus, in 191 selected countries, according to information from the virtual platform “datosmacro.com”. To meet the objective, the indicators of confirmed cases, deaths, lethality, and death rates from COVID-19 per million inhabitants were used. Data up to 08/29/2022 indicates that absolute deaths from COVID-19 by country is not the most appropriate indicator to assess the impact of the health crisis between nations. For its part, the fatality rates equivalent to deaths from COVID-19 among the total number of cases confirmed by SARS-CoV-2, is a good indicator, but it depends largely on the capacity of the health systems of each country. Deaths from COVID-19/million inhabitants, despite certain weaknesses, represents the best indicator to assess which nations have been most impacted by COVID-19 by continent and in the global context. An example is the comparison between Peru and the USA, where the Latin American country with an estimated population of 33,396,700 inhabitants, with 215,514 deaths; while the USA with a population of 332,183,000 inhabitants, with 1,043,840 deaths, although it is true that it is the nation with the highest number of deaths in the world, its death rate associated with COVID-19/million inhabitants up to 29 /08/2022 was 3,142.36, which was lower than that of Peru with 6,463.00. In conclusion, Peru was the most impacted by the COVID-19 crisis in the global context, followed by Bulgaria, North Macedonia, Bosnia and Herzegovina, Hungary, Georgia, Moldova, Montenegro, Croatia and the Czech Republic.